Digital logic testing and simulation - Miczo, Alexander (Wiley-Interscience, 2003)
The increase in the size and complexity of circuits on a chip with little or no increase in the number of Input/Output pins has made the need for testing ever more important. The test must detect failures in individual units, as well as failures caused by defective manufacturing processes. Random defects that go undetected may result in expensive recalls and also endanger the public, since digital logic devices have become pervasive in products that affect public safety, including applications such as transportation and human implants among others. This thoroughly revised edition of the author.